Measurement and modeling of self-broadening coefficients of the ν3 and 2ν3-ν3 bands of methyl chloride. (September 2019) - Dridi, N.; Maaroufi, N.; Manceron, L.; Rotger, M.; Aroui, H.
Highlights: Self-broadening coefficients have been measured in the ν3 and 2ν3 -ν3 bands of CH3 Cl. The rotational dependencies of broadening coefficients were analyzed. The data are modeled using a second-order empirical polynomial. Broadening coefficients were predicted using the Robert and Bonamy formalism with parabolic and exact trajectory models. The RBE model is not necessary for calculations of self-broadening of CH3 Cl even at low temperature. Abstract: High-resolution Fourier Transform spectra have been recorded at room temperature in the frequency region around 13 µm using a high-resolution Fourier transform spectrometer (Bruker IFS 125-HR). Transitions of both 12 CH3 35 Cl and 12 CH3 37 Cl isotopologues belonging to the P, Q and R branches of the ν3 and 2ν3 -ν3 parallel bands have been analyzed to retrieve self-broadening coefficients using a multispectrum fitting procedure that allowed to fit simultaneously the whole set of the experimental spectra recorded at seven pressures of CH3 Cl ranging from 1.02 to 10.24 mbar. Line positions were also derived using a wavenumber calibration performed by the frequencies of OCS transitions. About 2028 lines with 2 ≤  J  ≤ 59 and 2 ≤  K  ≤ 13 have been studied. The rotational J and K dependencies of the self-broadening coefficients have been clearly observed and modeled using a second-order empirical polynomial. The average accuracy of the line parameters has been estimated to be about 4 and 5% for the ν3 and 2ν3 -ν3 bands, respectively. Using the Robert and Bonamy formalism with parabolic and exact trajectory models, these coefficients were calculated, showing the predominance of the dipole-dipole interaction. The J and K rotational dependencies are consistent with the measured data. The predicted values confirm that the use of the exact trajectory model does not improve the predicted linewidths for a molecule with a large dipole moment such as CH3 Cl.